2020
DOI: 10.4111/icu.2020.61.4.425
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of a home-based, guardian-conducted video voiding test for voiding evaluation after hypospadias surgery

Abstract: Purpose: To investigate the validity and reliability of a home-based, guardian-conducted video voiding test for assessing postoperative voiding function after hypospadias surgery. Materials and Methods: In a single center, patients who had undergone urethroplasty by a single surgeon and postoperative uroflowmetry and video voiding tests conducted between 2008 and 2016 were retrospectively reviewed. Urinary stream was categorized into five grades by three pediatric urologists in a blinded manner. The primary ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…There are some studies that have already used a similar approach to that of our study. Previously, Han et al [ 10 ] studied the validity and reliability of guardian-conducted voiding videos for postoperative evaluation following hypospadias surgery. In their study, it was shown that the videos taken by the guardians were acceptable and beneficial for home-based postoperative assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some studies that have already used a similar approach to that of our study. Previously, Han et al [ 10 ] studied the validity and reliability of guardian-conducted voiding videos for postoperative evaluation following hypospadias surgery. In their study, it was shown that the videos taken by the guardians were acceptable and beneficial for home-based postoperative assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Merriman et al [ 7 ] showed that complete agreement for a scoring system among clinicians could only be achieved in 78%-85% of their cases. Therefore, some studies utilized photos and videos to help diagnose hypospadias [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%